Probabilistic Analysis of Hazard Soil Movement Based on Maximum Ground Acceleration Spectrum Patterns Due to the Malang Raya Earthquake - Marbun, Yorgita Naully; Basid, Abdul; Ilham, Ilham; Ginting, Rika Adelina; Sunardi, Bambang (Journal of Physics and Its Applications, 2024)
Earthquakes occur when tectonic plates beneath the earth's surface shift due to pressure accumulated in rocks, releasing kinetic energy and causing earthquake waves. This study analyzes the potential risk of earthquake hazards using the Probabilistic Seismic Hazard Analysis (PSHA) method which is based on the calculation of the probability of earthquake occurrence and vibration intensity using data from 3 sources of subduction earthquakes, faults and background earthquake sources in the Malang Raya research area which is geographically located in the Indonesian archipelago with an active collision zone of the Indo-Australian plate with the Eurasian plate. Research processing uses Zmap and R Crisis software. The results of the study show that peak ground acceleration has a value on the bedrock ranging from 0.169 g to 0.255 g. The ground acceleration spectrum at T = 0.2 seconds ranges from 0.288 g to 0.464 g, while at T = 1 second ranges from 0.150 g to 0.275 g. The distribution of PGAm values on the surface ranges from 0.174 g to 0.273 g, and the ground acceleration spectrum at T = 0.2 seconds ranges from 0.302g to 0.551g, while at T = 1 second it ranges from 0.151 g to 0.284 g. The area that shows the highest earthquake vulnerability value is around the southern coast of Malang Raya because it is close to the earthquake source. The northern region experiences an increase in the acceleration spectrum value due to its proximity to the source of the fault earthquake and several other geophysical factors.